"UZBEK LANGUAGE - THE SPIRIT AND PRIDE OF THE NATION" IT IS THE DUTY OF EACH OF US TO PROTECT OUR NATION (Archive of Conferences, 2021)
In this article we will discuss how invaluable and vivid the Uzbek language is, its rules and rules of writing are widely spread and applied among young people